2010
DOI: 10.1111/j.1365-2753.2009.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Tai chi for lowering resting blood pressure in the elderly: a systematic review

Abstract: The evidence for tai chi in reducing BP in the elderly individuals is limited. Whether tai chi has benefits over exercise is still unclear. The number of trials and the total sample size are too small to draw any firm conclusions. Further rigorous RCTs are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 37 publications
1
23
1
1
Order By: Relevance
“…Of the nine high-quality SRs,5 9 11 13 14 17 21 24 32 one arrived at a positive conclusion,11 five arrived at a negative conclusion,5 13 14 17 24 and in three SRs,9 21 32 no clear conclusions were drawn.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Of the nine high-quality SRs,5 9 11 13 14 17 21 24 32 one arrived at a positive conclusion,11 five arrived at a negative conclusion,5 13 14 17 24 and in three SRs,9 21 32 no clear conclusions were drawn.…”
Section: Resultsmentioning
confidence: 93%
“…Seven SRs concluded that the current data were insufficient to draw firm conclusions,8 10 21 25 29 32 37 eight SRs concluded that t'ai chi did not have a beneficial effect,5 6 13 14 17 20 24 26 and 20 SRs concluded that t'ai chi might be effective 7 8 11 12 15 16 18 19 22 23 27 28 30 31 3336 38 39. Of the nine high-quality SRs,5 9 11 13 14 17 21 24 32 one arrived at a positive conclusion,11 five arrived at a negative conclusion,5 13 14 17 24 and in three SRs,9 21 32 no clear conclusions were drawn.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, the increasing prevalence of hypertension creates a broad market for alternative therapy to aid the management of blood pressure [8]. Several CAM clinical studies, including a substantial number of randomized controlled trials (RCTs) and systematic reviews, have shown that CAM is effective and safe for the treatment of hypertension [912]. It can also improve appetite, intestinal motility, metabolism, and emotional factors such as stress.…”
Section: Introductionmentioning
confidence: 99%